Advances in understanding migraine pathophysiology: a bench to bedside review of research insights and therapeutics - Frimpong-Manson, Kofi; Ortiz, Yuma T.; McMahon, Lance R.; Wilkerson, Jenny L. (Frontiers in Molecular Neuroscience, 2024)
The individual and global burden of migraine is of such significance that there are accelerated efforts to develop new therapies. New migraine therapeutics are needed to address the current deficiencies that exist in the efficacy and adherence rate of approved anti-migraine medications. The recent discovery of the calcitonin gene related peptide as an add-on to the role of serotonin has markedly increased the range of new treatment options for acute and chronic migraine. Despite this, tackling the complexity of migraine disorders requires a complete understanding of its pathophysiology. Preclinical animal models can shed light on disease-related pathophysiology, including migraine. Indeed, the use of animal models has been instrumental in developing many therapeutics. However, an animal model is limited by the predictive and face validity of that model, and this extends to preclinical migraine models. In this review, a summary of the current understanding of the pathophysiology of migraine is given from both a preclinical and clinical perspective, and an emphasis is placed on the animal models